The influence of taxes, company size, foreign ownership and bonus mechanisms on transfer pricing (empirical study on mining sector companies listed on the Indonesian Stock Exchange in 2017-2021) - Nurmalasari , Erni; Wiharno, Herma; Dwi Martika, Lia (Lembaga Penelitian Universitas Swadaya Gunung Jati, 2023)
This study aims to understand, analyze and obtain empirical evidence that can explain the effect of taxes, firm size, foreign ownership and bonus mechanism on transfer pricing. The research method used in this research is descriptive method and verification method. The population in this study is the mining sector companies listed on the Indonesian stock exchange (IDX) in 2017 – 2021. A sample obtained by using a sampling quota of 35 companies or 175 financial report data. The analytical technique used in this study is logistic regression analysis using SPSS 20. The research results show that taxes, company size, foreign ownership, and bonus mechanisms simultaneously affect transfers pricing. test results partially show that the tax, company size, foreign ownership, and bonus mechanisms have a significant positive effect on transfer pricing.